Elastic stable intramedullary nail combined with Kirschner wire (E-K) technique for treating pediatric distal tibial diaphyseal metaphyseal junction (DTDMJ) fractures - Yunlong Liu; Sheng Ding; Yancai Yang (Frontiers Media S.A., 2024)
ObjectiveElastic stable intramedullary nail (ESIN) is a commonly used method for treating diaphyseal fractures of the tibia, but its application in Distal Tibial Diaphyseal Metaphyseal Junction (DTDMJ) fractures has been a subject of controversy. This study aims to evaluate the clinical efficacy of the Elastic stable intramedullary nail-Kirschner wire (E-K) technique in treating pediatric DTDMJ fractures, providing better clinical decision-making for clinicians in diagnosing and treating such fractures.MethodsWe conducted a retrospective analysis of patients aged 3-9 years who received treatment at our hospital from January 2019-January 2021 for distal tibial diaphyseal metaphyseal junction (DTDMJ) fractures. Based on their surgical procedures, they were categorized into the Elastic Stable Intramedullary Nail-Kirschner wire group (E-K) and the ESIN group. Demographic data, surgical duration, clinical outcomes, complications, and imaging data were recorded.ResultsThe study included a total of 57 patients, with 24 cases in the E-K group and 33 cases in the ESIN group. There were 30 males and 27 females. The average age was (6.25 ± 1.59) years in the E-K group and (6.27 ± 1.48) years in the ESIN group. There were no significant differences between the two groups in terms of gender, age, weight, time from injury to surgery, follow-up time, side of injury, associated injuries, nail site infection, deep infection, and nail removal time (P > 0.05). Neither group experienced nonunion or refracture. The E-K group exhibited significantly lower coronal and sagittal plane angular values at the final follow-up compared to the ESIN group (P < 0.001). In the E-K group, the final follow-up coronal plane angle was 2.67 (1.09)°, while in the ESIN group, it was 6.55 (2.05)°. The final follow-up sagittal plane angle was 3.12 (1.54)° in the E-K group and 7.58 (1.48)° in the ESIN group. Both groups showed good alignment in the initial postoperative x-rays, with no statistically significant differences. However, during clinical healing, the ESIN group exhibited significant displacement, whereas the E-K group had minimal displacement, demonstrating a significant statistical difference (P < 0.001). There was a statistically significant difference in the AOFAS joint function assessment between the two groups (P = 0.027).ConclusionThe E-K technique is a viable option for treating DTDMJ fractures in pediatric patients, with well-established clinical efficacy. Its advantages include a straightforward surgical procedure, safety, and a low incidence of severe complications.